PENGGUNAAN MEDIA PEMBELAJARAN DIGITAL BERBASIS APLIKASI SCRATCH UNTUK MENINGKATKAN HASIL BELAJAR IPAS PESERTA DIDIK KELAS V SD NEGERI GUE GAJAH ACEH BESAR - Darman Saputra; Linda Vitoria; Suci Fitriani (Jurnal Pesona Dasar, 2026)
This research was motivated by the low learning outcomes of fifth-grade students in the subject of Natural and Social Sciences (IPAS), particularly on the topic of classifying animals based on their types of food at SD Negeri Gue Gajah, Aceh Besar Regency. One of the causes was the use of conventional teaching methods and the lack of interactive learning media utilization. This study aimed to improve teacher activities, student learning activities, and students’ learning outcomes through the use of digital learning media based on the Scratch application. The research employed Classroom Action Research (CAR) conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of the study were the teacher and 20 fifth-grade students of SD Negeri Gue Gajah. Data collection techniques included observation and learning outcome tests. The data were analyzed using descriptive quantitative and qualitative methods. The results showed significant improvements in all observed aspects. Teacher activity increased from 47% in the sufficient category in Cycle I to 92% in the very good category in Cycle II. Student activity improved from 42% in the sufficient category to 82% in the very good category. Students’ learning outcomes also improved, with the average score increasing from 41.65 in Cycle I to 84.00 in Cycle II, while classical learning completeness increased from 5.8% to 95%. Based on these findings, it can be concluded that the use of Scratch-based digital learning media was effective in improving the activities and learning outcomes of fifth-grade students in IPAS at SD Negeri Gue Gajah, Aceh Besar Regency.